2005
DOI: 10.1074/jbc.m504545200
|View full text |Cite
|
Sign up to set email alerts
|

An Intersubunit Zinc Binding Site in Rat P2X2 Receptors

Abstract: P2X receptors are ATP-gated ion channels made up of three similar or identical subunits. It is unknown whether ligand binding is intersubunit or intrasubunit, either for agonists or for allosteric modulators. Zinc binds to rat P2X 2 receptors and acts as an allosteric modulator, potentiating channel opening. To probe the location of this zinc binding site, P2X 2 receptors bearing mutations of the histidines at positions 120 and 213 were expressed in Xenopus oocytes. Studies of H120C and H213C mutants produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 33 publications
8
91
0
Order By: Relevance
“…Unlike what we have seen previously with the double mutant P2X 1 receptors (Marquez-Klaka et al 2007), a strong monomeric band (50.6 § 0.2% of the total P2X protein) of the P2X 2 K69C/F289C subunits remained, indicating that the cross-linking was less eVective than in P2X 1 Rs. A faint additional band corresponding in size to a tetramer has also been observed previously and most likely represents an incompletely cross-linked trimer (Nagaya et al 2005;Marquez-Klaka et al 2007). In support of this interpretation, only complexes corresponding to trimers were detected by BN-PAGE analysis of metabolically labelled P2X 1 complexes (Marquez-Klaka et al 2007) and P2X 2 complexes (not shown).…”
Section: Resultsmentioning
confidence: 74%
“…Unlike what we have seen previously with the double mutant P2X 1 receptors (Marquez-Klaka et al 2007), a strong monomeric band (50.6 § 0.2% of the total P2X protein) of the P2X 2 K69C/F289C subunits remained, indicating that the cross-linking was less eVective than in P2X 1 Rs. A faint additional band corresponding in size to a tetramer has also been observed previously and most likely represents an incompletely cross-linked trimer (Nagaya et al 2005;Marquez-Klaka et al 2007). In support of this interpretation, only complexes corresponding to trimers were detected by BN-PAGE analysis of metabolically labelled P2X 1 complexes (Marquez-Klaka et al 2007) and P2X 2 complexes (not shown).…”
Section: Resultsmentioning
confidence: 74%
“…Although we have not determined the coordinating residues responsible for this weak and rapidly reversible potentiation in the wild-type channel, a simple explanation that would be consistent with the present study is that H33 and C348C can form a weak intrasubunit Cd 2+ bridge that stabilizes the open state. Concatamers were constructed as described previously (7,37,38) and were confirmed by restriction digests and DNA sequencing. In addition, cell lysates were evaluated with SDS/PAGE and Western blot analysis, which confirmed that the most abundant species of rP2X2 receptors in HEK cells expressing the concatenated trimeric construct corresponds to the molecular weight of a trimer (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Upon ATP binding, structural rearrangements of the subunit interface (3)(4)(5) lead to the opening of the ion channel (6)(7)(8), but the entire molecular sequence of events that couple ATP binding to channel opening remains unknown. The recent X-ray structure of the P2X4 receptor in a closed resting state represents in this regard a decisive step (9).…”
mentioning
confidence: 99%